2015
DOI: 10.18227/1982-8470ragro.v9i3.2336
|View full text |Cite
|
Sign up to set email alerts
|

Ecofisiologia de mangueiras‘Tommy Atkins’submetidas a diferentes regimes hídricos e disponibilidade de luz

Abstract: Resumo: A interação entre o déficit hídrico e o mau aproveitamento de radiação luminosa pelas plantas pode ocasionar redução nas trocas gasosas e, consequentemente, diminuir o seu crescimento e sua produção. Em mangueira 'Tommy Atkins', os estudos sobre essa interação são escassos. Diante do exposto, objetivouse avaliar variáveis ecofisiológicas em folhas de mangueiras 'Tommy Atkins' submetidas a variações de luminosidade e de regime hídrico na copa, em diferentes horários. Os dados foram analisados em delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…Regarding production, there was interaction between phenological stages and production cycles (Figure 3). The first production cycle showed higher temperatures, resulting in higher gas exchange and higher photosynthetic production than the second cycle, which resulted in higher fruit production, as also observed in 'Tommy' mango by Almeida et al (2015). According to Taiz et al (2017), the increase in stomatal conductance may lead to a higher CO 2 influx in leaf In the first cycle, the highest production of 'Kent' mango was estimated at 44.6 and 48.4 kg plant -1 for the irrigation depths of 83.37 and 72.76% ETc, in the F2 and F3 stages, respectively.…”
Section: Resultsmentioning
confidence: 55%
“…Regarding production, there was interaction between phenological stages and production cycles (Figure 3). The first production cycle showed higher temperatures, resulting in higher gas exchange and higher photosynthetic production than the second cycle, which resulted in higher fruit production, as also observed in 'Tommy' mango by Almeida et al (2015). According to Taiz et al (2017), the increase in stomatal conductance may lead to a higher CO 2 influx in leaf In the first cycle, the highest production of 'Kent' mango was estimated at 44.6 and 48.4 kg plant -1 for the irrigation depths of 83.37 and 72.76% ETc, in the F2 and F3 stages, respectively.…”
Section: Resultsmentioning
confidence: 55%
“…Among these, vapor pressure deficit is the most relevant. According to Almeida et al (2015), vapor pressure deficit can portray crop water stress, as well as plasticity in water use. In this sense, points with higher garlic yields coincided with those with lower VpdL, whose greatest trends were to the north of the map (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the initial characterization of the plants (Start), the leaf soluble carbohydrates concentration before the treatment application was slightly higher than the concentrations obtained after the application of the treatments, a fact that may be linked to the imposition of water stress during this period. Almeida et al (2015) reported that one of the water stress effects on plants is the lower vegetative growth, promoting the accumulation of reserves.…”
Section: Resultsmentioning
confidence: 99%
“…According to Almeida et al (2015), plants under water stress tend to reduce photoassimilate production and consume the accumulated amount but, on the other hand, when water is adequately supplied there is signaling for ordinary metabolism and, consequently, photoassimilate accumulation. For the last evaluation date, T5 had a higher average carbohydrate concentration, but without significant difference from the other treatments (Figure 3).…”
Section: Resultsmentioning
confidence: 99%